TINJAUAN SISTEM KERJASAMA PENGELOLAAN LAHAN PERTANIAN DALAM PERSPEKTIF EKONOMI ISLAM: (STUDI KASUS DI DESA MAJA KECAMATAN MARGA PUNDUH KABUPATEN PESAWARAN PROVINSI LAMPUNG) - Murnasih, Murnasih; Iswandi, Irvan; Fitri, Ahmad Asrof (Journal of Islamic Studies, 2023)
The local community often cooperates in the management of agricultural land between land owners and land managers. Because not all landowners are able to manage their land and have knowledge of agricultural management. On the other hand, not everyone who has knowledge in land management owns land, so there is a process of cooperation between the two parties to generate mutual benefits. The majority of residents in Maja Village work as farmers. The author is interested in researching the cooperative system of agricultural land management in Maja Village, Marga Punduh District, Pesawaran Regency, Lampung Province, especially from the perspective of Islamic law. The research approach used was descriptive qualitative with in-depth interview techniques with informants. The techniques used in the data collection process were through interviews, observation, and documentation. The results of this study indicate that in conducting agricultural land management cooperation contracts between landowners and cultivators only verbally, not in writing. In addition, there is no time limit for the end of this cooperation in land management.